An environmentally friendly process to selectively recover silver from copper anode slime. (20th June 2018) - Xiao, L.; Wang, Y.L.; Yu, Y.; Fu, G.Y.; Han, P.W.; Sun, Z.H.I.; Ye, S.F.
Abstract: Anode slime is an important secondary resource for recovery of silver. However, high energy consumption and serious pollution limit the recovery with current processes. In this study, an effective and environmentally friendly process was developed for selective recovery of silver from copper anode slime, which consisted of oxidative pretreatment-thiosulfate leaching-electrodeposition. By using this novel strategy, silver recovery reached 96% with low consumption of reagent and energy, which also avoided emissions of harmful gases, such as sulfur dioxide and ammonium. The effects of pretreatment on phase conversion of silver and sulphur compounds in anode slime, the re-precipitation of silver during leaching were investigated, and efficiencies of the lixiviants of thiosulfate, sulfite and ammonia were compared in silver recovery. Meanwhile, the silver electrodeposition and electrolyte recycling were also investigated. It was demonstrated that the silver recovery from thiosulfate leaching solution by utilizing electrodeposition reached to 99.9% and a 95.3% recovery obtained by recycling the electrolyte for silver leaching. The study developed an effective green process to recover silver from anode slime. Graphical abstract: Image Highlights: A novel process for silver recovery from anode slime is proposed. MnO2 is effective for the conversion of sulfide to sulfate. Thiosulfate is more efficient than ammonia and sulfite in silver recovery. Electrodeposition is proposed for the silver reduction from leaching solution.